2021
DOI: 10.1016/j.mayocpiqo.2020.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Digital Health Surveillance Strategies for Management of Coronavirus Disease 2019

Abstract: Objective: To describe the design, implementation, and utilization of electronic health record (EHR)e based digital health surveillance strategies used to manage the coronavirus disease 2019 (COVID-19) pandemic and to ensure delivery of high-quality clinical care, such as case identification, remote monitoring, telemedicine services, and recruitment to clinical trials at Mayo Clinic. Methods: The design and implementation work described in this report was performed at Mayo Clinic, a large multistate integrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…6 Also, COVID-19 diagnosis in our study was confirmed using a diagnostic PCR test. 7 This analysis is subject to the limitations common to observational cohort studies, for example, inclusion of some, but likely not all, confounding variables (ie, related both to COVID-19 risk and e-cigarette use). Study participants were a convenience sample who presented for outpatient care to Mayo Clinic's ambulatory clinics, a sample that may not be entirely representative of the population of e-cigarette users in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Also, COVID-19 diagnosis in our study was confirmed using a diagnostic PCR test. 7 This analysis is subject to the limitations common to observational cohort studies, for example, inclusion of some, but likely not all, confounding variables (ie, related both to COVID-19 risk and e-cigarette use). Study participants were a convenience sample who presented for outpatient care to Mayo Clinic's ambulatory clinics, a sample that may not be entirely representative of the population of e-cigarette users in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of COVID-19 within this period was ascertained using COVID-19 registry data as previously described. 7 All patients with current or former history of SARS-CoV-2 infection (a positive SARS-CoV-2 test or active infection record in EHR or a diagnosis of COVID-19 on the problem list of the EHR) are included in this validated registry. 7 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An integrated model of digital disease management might considerably relieve the burden to ambulatory health care, if it is implemented as an interoperable digital solution following evidence-based medical knowledge, operated by addressing the personal needs of patients, and hosted by an approved medical body. 147 , 148 This model requires the following considerations: the patient must have access to evidence-based health information in a language adjusted for health literacy, there must be medical indicators representing the therapeutic goal or corridor for patients, such an indicator must be technically measurable, and the patient must have a therapy that can be adjusted by patient self-management. Applying smart digital disease management might have the potential to substantially reduce the throughput in the ambulatory health-care system.…”
Section: Long-term Consequences and Monitoring After Covid-19mentioning
confidence: 99%
“…Patients' data collected through EHR can be used in research and provide an opportunity to study diseases and extract clinical knowledge. 57 Integrating EHR with other systems and software, including mobile apps, can further enhance its potential benefits. When apps are integrated with the EHR, they fully optimize its efficiency.…”
Section: Discussionmentioning
confidence: 99%